Brownian motion in a euclidean space with a membrane located on a given hyperplane - Kopytko, B.I.; Portenko, M.I. (Reports of the National Academy of Sciences of Ukraine, 2022)
For the Brownian motion in a Euclidean space, a membrane located on a given hyperplane and acting in the normal direction is constructed such that its so-called permeability coefficient can be given by an arbitrary measurable function defined on that hyperplane and taking on its values in the interval [–1, 1]. In all the previous investigations on the topic that coefficient was supposed to be a continuous function. A limit theorem for the number of crossings of the hyperplane by a discrete approximation of the process constructed is proved. A curious interpretation for the limit distribution in that theorem can be given in the case of the membrane being porous.